The Development of MSMEs in India: a Bibliometric Analysis - Kalwad, Ayubkhan; Kumar J.P, Senthil (Journal of Ecohumanism, 2024)
This paper aims to evaluate the structure and evolutionary trend of research on development in MSMEs in India using a bibliometric examination. An analysis of academic research from 2008 to 2022 was conducted using bibliometric methods, searching for the terms used in emergent technologies. The research is intended to assess the development of micro, small, and medium companies and understand how far this topic has been achieved. Several research methods were applied, including the network method, thematic maps, and coefficients of approaching or intellectual tools. The result of this work can be helpful for new scholars and current trends, based on the study trends to achieve sustainable development goals against poverty, micro MSMEs (Micro Small Medium Enterprises), and unemployment. The highlight of the report stresses on the key issues where researchers are giving more focus which includes innovation and supply chain strategies. The findings from the study serve to enhance our understanding about areas within the extant research literature where less is known, particularly when it comes to advances and barriers that impact Micro, small-and medium enterprises (MSMEs). The present study will imbibe researchers and the experts from industry to have a profound insight into intellectual domains surrounding certain technologies that can facilitate growth of MSMEs in India, as well provide above detailed unattended research scope. The research concerning MSMEs has undoubtedly provided many facts about the growth and development of these enterprises, applicable particularly in India. To describe the research and intellectual progress on the Manufacturing industry, a bibliometric approach was used in this study. A comprehensive literature review and meta-analysis were employed to get trustworthy results.